Transforming urban-rural water linkages into high-quality investments. - Asian Development Bank. ([Manila] Asian Development Bank, 2020)
This publication describes and discusses the urban-rural water linkages (URWLs) approach to restoring river health in degraded environments. It emphasizes how the approach tackles issues relevant to land use, water withdrawal, and pollution. The URWLs approach can be effectively embedded into the project design to maximize the benefits of investment projects, which are aimed at restoring degraded river environment and uplifting the livelihood of the people dependent on such ecosystem. In this regard, the publication makes a case for how it can be applied generally across ADB developing member countries.
Keywords: Water supply -- Accounting -- Asia; Water supply -- China -- Dengzhou Shi (Henan Sheng).; Electronic books